OPTIMALISASI SANTRI SADAR KESEHATAN DAN OBAT DI PONDOK PESANTREN MAHASISWA - wasito, Hendri; sa'dudin, Ihsan; Fareza, M. Salman; Rehana (Jurnal Bakti untuk Negeri, 2024)
Health-related problems in Islamic boarding schools or Pesantren rarely get the attention of its residents and the surrounding community. An-Najah Student Islamic Boarding School is one of the Islamic boarding schools in the Banyumas area. In the health sector, the student or santri have not been optimal in paying attention to the health of the surrounding environment both in dormitories and dorm rooms. Therefore, health efforts in the form of promotive, preventive and curative were needed. The purpose of community service activities was to increase the knowledge and awareness of santri as well as the management of Pesantren related to health and proper management of medicines. In addition, activities were also carried out to improve facilities and infrastructure to support health in realizing clean and healthy Islamic Boarding Schools. The activity was carried out by adopting the Guidelines for the Implementation and Development of Islamic Boarding Health Units that had been issued by the Indonesian Ministry of Health in 2013. The results of community service activities were in the form of increasing awareness and knowledge of the students on proper health and drug management and improving health facilities and infrastructure in Islamic Boarding Schools.